THE USE OF COMPLEX SENTENCES AND THE PROBLEM OF THEIR TRANSLATION IN INTERNATIONAL AGREEMENTS - Mirijanyan, Varduhi (Foreign Languages for Special Purposes, 2024)
This article is devoted to the study of complex sentences used in official legal documents. The use of complex syntactic structures is a must (mandatory) in formal writing. When there is a need to make the speech multi-content and full of information, the use of complex structures (sometimes with more than a dozen components) is simply inevitable. Therefore, the syntactic study of special multi-component connections characteristic of legal official style in general and the functional manifestation of documents and contracs in particular – is a necessary prerequisite for understanding the mentioned discourse variety. It is obvious that the translator should be familiar with all the types and forms of complex sentence structure in order to first understand the English meanings and then accurately present them in the Armenian translation.
Keywords: legal language; legal document; complex sentences and structures; translation; semantic accuracy